The Relevance of industrial Practice Activities to the Competency Field of Industrial Practice in Faculty of Engineering YSU - Moh Adam Jerusalem; Putut Hargiyarto; Mashoedah Mashoedah (LPPM UNY, 2013)
This study is aimed at finding out the comparasion between students' activities in industrial practice and the curriculum of industrial practice. The study was a survey. The population consisted of students of the Engineering Faculty taking industrial practice in 2011. A sample of 268 students was used. The results of the study show that all the activities of industrial practice of all study programs have suitable correspondence with the curriculum of industrial practice. On assistancy side, industry used discussion, supervision, and giving material as the methods of assistancy. The majority of the industries made use of the discussions that went on when students put up questions to supervisors.